Countrywide distribution of fauna association with the cassva green mite (Mononychellus tanajoa) in Cameroon - Tchuanyo, M.; Yaninek, John S.; Hammond, W.; Onzo, A.; Lienou, L. (African Journals Online, 2007)
A survey of the distribution and abundance of cassava green mite and associated indigenous natural enemies found in the cassava agroecosystem in Cameroon was conducted during the 1991 dry season (January-February). The survey area included nine of the ten provinces of the country and covered 4.2 km. The list of pests, weeds and local phytoseiids found on cassava and associated crops/weeds in 46 fields is presented. Twenty four species of phytoseiid mites were recorded, with Typhlodromalus saltus mostly found on cassava while Typhlodromips shi was more prevalent on weeds and fruit trees. The densities of M. tanajoa in the regions are also determined. This pest was found everywhere, with the highest densities in the Highland savannah (230 actives/leaf) and transitional zone (143 actives/leaf). These densities remained high despite the presence of local phytoseiids. The lowest densities were recorded in the forest zone (5 actives/leaf). No mites (either phytophagous or predaceous) were found in the Northern region. There is need to introduce exotic phytoseiids to control the M. tanajoa populations in Cameroon. A classical biological control program, combined with other compatible control methods such as cultural practices and host plant resistance, is recommended to combat this exotic pest in Cameroon.